Efektivitas Video Animasi Sebagai Upaya Peningkatan Pengetahuan Dasar Pasien Diabetes Melitus - Fatihah, Dalillah Mustika; Juliani, Enni; Panjaitan, Ribka S (Jurnal Pustaka Keperawatan (Pusat Akses kajian Keperawatan), 2025)
Diabetes mellitus is a chronic disease that requires a comprehensive understanding from patients to prevent complications. However, conventional health education often proves to be less effective in increasing patient knowledge. This study aims to determine the effectiveness of using animated videos as an educational medium to improve the basic knowledge of diabetes mellitus patients at the Sawah Besar Community Health Center. The research employed a true experimental design with a post-test only control group approach involving 116 respondents divided into two groups: intervention and non-intervention. The instrument used was the DKQ-24 questionnaire, with data analysis using the Mann-Whitney test. The results showed that the majority of respondents in the intervention group (72.4%) had good knowledge, while in the non-intervention group, most (91.4%) fell into the low knowledge category. The statistical test revealed a significant difference between the two groups (p = 0.000). In conclusion, animated videos are effectively used as an educational medium to enhance the basic knowledge of patients with diabetes mellitus because they can convey information in an engaging, easily understandable manner, and reach various backgrounds of respondents.